Animals, rights, and legal personhood - Weber, Shayne, author; Lopez, Andrew, advisor; Gorin, Moti, committee member; Hempel, Lynn, committee member (Colorado State University. Libraries, 2025)
This thesis serves as an intervention in debates between supporters of Animal Rights and supporters of Animal Welfare and their relationship to the law. Specifically, I consider whether nonhuman animals must be recognized as persons under the law in order to have rights. I review the most prominent accounts put forth by theorists of Animal Rights and Animal Welfare. I then draw from recent work in Animal Rights to clarify a conceptual confusion over what is meant by a right that leads theorists to speak past each other. Having clarified this confusion, I argue that animals should be granted the right to liberty, and consequently recognized as legal persons, because they have an interest in liberty. I then extrapolate on the implications my argument would have for our relationships with different animals.
Keywords: animal welfare; legal rights; legal personhood; animal rights